Fundamental Loading‐Curve Characteristics of the Persistent Phosphor SrAl2O4:Eu2+, Dy3+, B3+: The Effect of Temperature and Excitation Density. Issue 4 (12th January 2022) - Delgado, Teresa; Gartmann, Nando; Walfort, Bernhard; LaMattina, Fabio; Pollnau, Markus; Rosspeintner, Arnulf; Afshani, Jafar; Olchowka, Jacob; Hagemann, Hans
Abstract : The compound SrAl2 O4 :Eu 2+, Dy 3+ is currently one of the best‐performing persistent phosphors and numerous studies have been performed to understand the mechanisms involved in its afterglow process. One aspect which so far has received only limited attention is the dependence of loading curve characteristics on dopant concentrations. Herein, a detailed study of the loading curves of SrAl2 O4 :Eu 2+, Dy 3+ as a function of composition, sample temperature, and pump intensity is presented, completed by emission decay and quantum yield measurements. The observed emission decays can be described using the Inokuti−Hirayama equation for a Dexter energy transfer (ET) process. As the Dexter ET rate and the electron transfer rate have a similar radial dependence, the Inokuti−Hirayama equation can also describe the electron transfer process involved for the trapping process. These observations indicate that in this persistent phosphor, the trapping process is a local process; however, different types of traps appear to present different "Dexter" critical radii R 0 . This electron transfer is also temperature dependent, which requires further investigations. Abstract : The charging profile of the persistent phosphor SrAl2 O4 :Eu 2+, Dy 3+, B 3+ depends on the excitation intensity, temperature, and the ratio between the concentration of Eu 2+ ions and the trap concentration, given among others by the Dy 3+ amount. The analysis of the luminescence decay curves suggests that the electron transfer process is local process.